Temperature response of permafrost soil carbon is attenuated by mineral protection. (1st June 2018) - Gentsch, Norman; Wild, Birgit; Mikutta, Robert; Čapek, Petr; Diáková, Katka; Schrumpf, Marion; Turner, Stephanie; Minnich, Cynthia; Schaarschmidt, Frank; Shibistova, Olga; Schnecker, Jörg; Urich, Tim; et al.
Abstract: Climate change in Arctic ecosystems fosters permafrost thaw and makes massive amounts of ancient soil organic carbon (OC) available to microbial breakdown. However, fractions of the organic matter (OM) may be protected from rapid decomposition by their association with minerals. Little is known about the effects of mineral‐organic associations (MOA) on the microbial accessibility of OM in permafrost soils and it is not clear which factors control its temperature sensitivity. In order to investigate if and how permafrost soil OC turnover is affected by mineral controls, the heavy fraction (HF) representing mostly MOA was obtained by density fractionation from 27 permafrost soil profiles of the Siberian Arctic. In parallel laboratory incubations, the unfractionated soils (bulk) and their HF were comparatively incubated for 175 days at 5 and 15°C. The HF was equivalent to 70 ± 9% of the bulk CO2 respiration as compared to a share of 63 ± 1% of bulk OC that was stored in the HF. Significant reduction of OC mineralization was found in all treatments with increasing OC content of the HF (HF‐OC), clay‐size minerals and Fe or Al oxyhydroxides. Temperature sensitivity (Q10) decreased with increasing soil depth from 2.4 to 1.4 in the bulk soil and from 2.9 to 1.5 in the HF. A concurrent increase in the metal‐to‐HF‐OC ratios with soil depth suggests a stronger bonding of OM to minerals in the subsoil. There, the younger 14 C signature in CO2 than that of the OC indicates a preferential decomposition of the more recent OM and the existence of a MOA fraction with limited access of OM to decomposers. These results indicate strong mineral controls on the decomposability of OM after permafrost thaw and on its temperature sensitivity. Thus, we here provide evidence that OM temperature sensitivity can be attenuated by MOA in permafrost soils. Abstract : The study investigated the temperature sensitivity of organic carbon in Siberian permafrost soils. The results showed that although substantial amounts of soil organic carbon are prone to degradation under rising global temperatures, strong mineral controls affect the temperature sensitivity of organic carbon mineralization. We here provide evidence that OM temperature sensitivity can be attenuated by mineral‐organic associations in permafrost soil.